PERTANGGUNGJAWABAN PIDANA DENGAN PRINSIP MIRANDA RULE DALAM BIDANG KESEHATAN DAN K3 RUMAH SAKIT - Sunariyo Sunariyo (Collegium Studiosum Journal, 2025)
The Miranda Rule is a fundamental principle in criminal law that guarantees the human rights of individuals facing legal proceedings. In the context of occupational health and safety (OHS) services in hospitals, the application of the Miranda Rule can be a challenge, given the often urgent and complex nature of health services. This article examines the application of the Miranda Rule principle in the criminal realm related to violations in the health and OHS fields in hospitals, and examines its implications for the criminal liability of health workers. This study aims to provide a comprehensive legal perspective by including a comparative analysis of several international jurisprudence. This article uses a normative juridical research method with three main approaches: 1) The statute approach, which examines laws and regulations relevant to this research topic; 2) The conceptual approach, which identifies the legal concepts and values ​​that underlie them, as well as those contained in the legal norms; and 3) The case approach, which aims to analyze applicable legal norms or rules based on relevant cases. The application of the Miranda Rule principle is very important to protect the rights of health workers in legal proceedings, especially in cases of Occupational Health and Safety (K3) violations in hospitals.